Estimating small structural motions from multi-view video measurement. (15th January 2023) - Cai, Enjian; Zhang, Yi; Ji, Xiaodong; Lu, Xinzheng; Xie, Linlin; Zhuang, Yuncheng; Zhao, Taisen; Lin, Guangwei
Highlights: Phase unwrapping step is established to increase the structural motion estimation range. A weighted least-squares phase unwrapping is developed in 2D structural motion estimations. The iteratively reweighted algorithm is utilized to enhance the multi-view structural motion estimation. Abstract: The phase-based estimation, as one type of target-free methods, can estimate small structural motions from video data. However, in the two-dimensional (2D) domain, this method is prone to noisy errors because of the ill-posed problem, and its measurement range is limited due to the periodicity of the phase variation. Additionally, it cannot estimate three-dimensional (3D) structural motions. To estimate 3D small structural motions more accurately, this paper proposed a novel multi-view video measurement method including 2 steps, namely weighted phase unwrapping and l q -norm minimization. The weighted phase unwrapping is to measure 2D small structural motions, in which the unweighted and weighted least-square formulations are established, and iteratively solved by the fast transforms. To project 2D structural motions into the 3D domain, the l q -norm multi-view minimization with the corresponding reweighted algorithm is developed. The proposed method was applied in the experiment of a 3-storey reinforced concrete (RC) structure under earthquake loads. Its validity was verified by the more accurate estimation of the structural motions from multi-view video measurement.